Perancangan IoT Sistem Pengukur Kekeruhan Air dan Pemberi Pakan Ikan Berbasis Android - Kostaman, Ade; Niswati, Za’imatun; Abdillah, Rahman (Universitas Indraprasta PGRI Jakarta, 2023)
Moving to the automation era is a big step in human civilization. The use of integrated automation technology with the help of internet connectivity, known as IoT, has helped a lot in human life. The aim of this research is to design a water turbidity measuring device and ornamental fish feeding sensor that can be controlled remotely using the Android-based internet. The research method used is an experimental method by conducting trials (trial error). Each module/sensor is tested one by one so that it can function as planned. Components tested include: Servo motor, ultrasonic sensor, turbidity sensor. Test result at a servo motor opening time is of 350 ms, the weight of the food released is 5.3 grams with an error percentage of 5.6%. When the servo motor is opened at 650 ms, the weight of the feed released is 10.2 grams with an error percentage of 2.4%. When the servo motor is open for 1000 ms, the weight of the food released is 15.2 grams with an error percentage of 1.84%. The ultrasonic sensor has an average error in detecting food residue of 3.01%, and the turbidity sensor detects turbidity by dividing it into 3 types of water, namely clear water, turbid water, and very turbid water. The results of the research are an Android-based water turbidity meter and ornamental fish feed sensor that can ensure fish food intake is adequate, especially when the owner travels far from home.